2020
DOI: 10.2471/blt.20.255943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of novel compounds against three targets of SARS CoV-2 coronavirus by combined virtual screening and supervised machine learning

Abstract: Coronavirus disease 2019 (COVID-19) is a major threat worldwide due to its fast spreading. As yet, there are no established drugs or vaccines available. Speeding up drug discovery is urgently required. We applied a workflow of combined in silico methods (virtual drug screening, molecular docking and supervised machine learning algorithms) to identify novel drug candidates against COVID-19. We constructed chemical libraries consisting of FDA-approved drugs for drug repositioning and of natural compound datasets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 51 publications
1
78
0
1
Order By: Relevance
“…Considering an urgent need of containing the pandemic, repurposing of previously approved drugs to use against SARS-CoV-2 is the first choice in the fight against this virus, as such drugs are not required to pass through most of the steps of an extensive drug testing process. In this regard, several recent studies have been conducted using computational methods to screen libraries of approved drugs or drug-like molecules to identify potential inhibitors of different viral proteins, particularly, RdRp and 3CL-protease [13][14][15][16][17]. Moreover, high throughput in vitro screening of FDA approved drug libraries followed by in vivo validation has also been applied on limited hits [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Considering an urgent need of containing the pandemic, repurposing of previously approved drugs to use against SARS-CoV-2 is the first choice in the fight against this virus, as such drugs are not required to pass through most of the steps of an extensive drug testing process. In this regard, several recent studies have been conducted using computational methods to screen libraries of approved drugs or drug-like molecules to identify potential inhibitors of different viral proteins, particularly, RdRp and 3CL-protease [13][14][15][16][17]. Moreover, high throughput in vitro screening of FDA approved drug libraries followed by in vivo validation has also been applied on limited hits [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, using BenevolentAI’s knowledge graph and a library of structured medical information, machine learning uncovered baricitinib, a Janus kinase inhibitor used for rheumatoid arthritis, as a safe candidate drug that could inhibit SARS-CoV-2 viral entry [ 27 ]. In another study, a similar process of virtual drug screening identified antiviral agents against hepatitis C as drugs that had high binding affinities to target proteins on SARS-CoV-2 [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…This compound is FDA approved for use in adult patients infected with HIV-1. Nevirapine has also been revealed in various in-silico drug screening with the main protease 115,116 . Pentostatin is a purine analog that is widely used as a treatment for hairy cell leukemia 117 .…”
Section: Resultsmentioning
confidence: 99%